Pendidikan Islam Homeschooling dalam Perspektif Pendidikan Islam Multi, Inter dan Transdisipliner - Fauzi Rahmani, Muhammad; Sabda, Syaifuddin (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This paper examines homeschooling Islamic Education in the point of view of multi, inter and transdisciplinary Islamic education. Multidimensional Islamic education entrusts integration in each of its components so that a complete, holistic and integral understanding is formed. The linearity of science and monodisciplinary approaches in the family of religious sciences will result in the understanding and interpretation of religion losing touch with its reality and relevance to the surrounding life to the issues studied. In this context, home-based Homeschooling model education and has flexibility in the learning process provides an alternative education that is expected to be able to concoct the concept of Islamic education that is multi, inter and transdisciplinary so that the goal of Islamic education to realize the generation of Insan Kamil can be achieved in addition to that Islamic homeschooling education has a syar'I basis and has historical links in its educational methods.